Pemberdayaan Anak Terlantar melalui Mini Project Sains Berbasis Fisika di Titik Penampungan Manggala Kota Makassar - Rifda Nur Hikmahwati Arif; Nurhayani H. Muhiddin; Fandi Ahmad; Salma Samputri; Iffat Sheril Fania (JKM: Jurnal Kemitraan Masyarakat, 2026)
Street children in Makassar City are a vulnerable group requiring support to strengthen knowledge and productive skills. This activity aimed to improve basic physics understanding and practical skills among children assisted by the Community Care for Street Children at the Manggala shelter point through science mini project training. The activity was conducted on September 14, 2024, involving approximately 25 elementary and junior secondary school-aged children. The implementation method included concept introduction, direct training in small groups, product-making assistance, and evaluation of participants’ work. The products developed were decorative lamps based on simple electric circuits and mini fans powered by solar panels. The results showed that participants were actively involved, able to assemble simple electric circuits, understood the principle of converting light energy into electrical energy, and produced functional products with potential economic value. This activity provided contextual science learning experiences while introducing simple entrepreneurial skills. Therefore, physics-based science mini projects can serve as a practical, enjoyable, and relevant empowerment strategy to support the independence of street children.